Biotransformation of Host Plant Flavonoids by the Fungal Endophyte Epicoccum nigrum. Issue 45 (2nd December 2019) - Harwoko, Harwoko; Hartmann, Rudolf; Daletos, Georgios; Ancheeva, Elena; Frank, Marian; Liu, Zhen; Proksch, Peter
Abstract: Fermentation of the fungus Epicoccum nigrum isolated from leaves of Salix sp. on green lentil solid medium yielded the flavonol kaempferol (3 ) as well as two kaempferol O ‐diglycosides (1 and 2 ) including the new compound 1 . The fungal flavonoids bear strong structural similarities to kaempferol derivatives such as kaempferol O ‐glycoside (4 ) being present in green lentils. Furthermore, feeding experiments were conducted by adding flavonoids (kaempferol and rutin) as precursors to solid rice media followed by HPLC and LC‐MS analyses. Fermentation of the fungus on flavonoid free solid rice medium afforded flavonoid free extracts indicating that the fungal flavonoids originate through hydrolytic cleavage of kaempferol glycosides such as 4 followed by glycosylation and acetylation. This study suggests that E. nigrum is capable of biotransformation reactions of plant derived flavonoids whereas de novo biosynthesis of flavonoids is less likely. Abstract : A fungal endophyte Epicoccum nigrum associated with willow leaves ( Salix sp.) is capable of biotransforming flavonoids that originated either from OSMAC (One Strain MAny Compounds) approach or from a feeding experiment with kaempferol. An OSMAC experiment was conducted through fermentation of this fungus on green lentil medium, while the latter experiment performed on solid rice medium, which resulted in the production of a new flavonol O ‐diglycoside and the other kaempferol derivatives.